Optimization of the Dyeing Conditions of Natural Dye from African Locust Bean (Parkia biglobosa) Pod on Cotton Fabrics - Andama Aaron Kanadi; Joshua Yakubu; James Yakubu; Abdulkadir Junior Bilyamin; Akinterinwa Ayo; Peter Micheal Dass (Kwaghe International Journal of Sciences and Technology, 2026)
This study examines the dyeing performance, color fastness, surface morphology, and antimicrobial properties of cotton fabrics dyed with natural dye extract, both with and without mordant treatment. The dye extract was applied to treated and untreated cotton fabrics, while CuSO₄, FeSO₄, and KAl(SO₄)₂ were used as mordants to produce different color shades. The optimum dyeing conditions for treated and untreated cotton fabrics were identified at dye concentrations of 2% and 1.5%, temperatures of 90°C and 80°C, and dyeing times of 60 and 50 minutes, respectively. Color fastness to washing and sunlight was evaluated, and the surface morphology of dyed and undyed fabrics was investigated using SEM. The dyed cotton fabrics demonstrated good color fastness, with ratings ranging from 3 to 5 under washing and sunlight exposure. Antimicrobial analysis showed that all dyed fabrics, with and without mordants, produced no inhibition zone against the bacteria Bacillus subtilis and Salmonella typhi, with values of 0.00 ± 0.00. However, the dyed fabrics exhibited varying inhibition zones against the fungus Penicillium notatum. Treated cotton dyed with copper sulphate mordant showed the highest inhibition zone of 1.1 ± 0.00 mm, whereas untreated cotton dyed with potassium aluminium sulphate mordant showed the lowest inhibition zone of 0.4 ± 0.00 mm. The study concludes that mordant-assisted dyeing can improve shade variation and maintain acceptable color fastness in cotton fabrics, while the antifungal activity of the dyed fabrics suggests potential functional value for naturally dyed textile applications.